Chronic nicotine attenuates behavioral and synaptic plasticity impairments in a streptozotocin model of Alzheimer's disease. (14th June 2017) - Esteves, I.M.; Lopes-Aguiar, C.; Rossignoli, M.T.; Ruggiero, R.N.; Broggini, A.C.S.; Bueno-Junior, L.S.; Kandratavicius, L.; Monteiro, M.R.; Romcy-Pereira, R.N.; Leite, J.P.
Highlights: STZ-icv induced dysfunction in CA1-mPFC plasticity and recognition memory. Nicotine was effective to prevent prefrontal LTP and memory deficits induced by STZ-icv. Modulation of nicotinic receptor might be an alternative approach for AD treatment. Abstract: Brain glucose metabolism is altered in sporadic Alzheimer's disease (sAD), whose pathologies are reproduced in rodents by intracerebroventricular (icv) infusion of streptozotocin (STZ) in subdiabetogenic doses. The icv-STZ model also culminates in central cholinergic dysfunctions, which in turn are known to underlie both the sAD cognitive decline, and synaptic plasticity impairments. Considering the cognitive-enhancing potential of chronic nicotine (Nic), we investigated whether it attenuates icv-STZ-induced impairments in recognition memory and synaptic plasticity in a cognition-relevant substrate: the hippocampal CA1-medial prefrontal cortex (mPFC) pathway. Rats treated with icv-STZ were submitted to a chronic Nic regime, and were evaluated for recognition memory. We then examined long-term potentiation (LTP), paired-pulse facilitation (PPF) under urethane anesthesia, and brains were also evaluated for hippocampus-mPFC cell density. We found that Nic treatment prevents icv-STZ-induced disruptions in recognition memory and LTP. STZ did not precipitate neuronal death, while Nic alone was associated with higher neuronal density in CA1 when compared to vehicle-injected animals. Through combining behavioral, neurophysiological, and neuropathological observations into the Nic-STZ interplay, our study reinforces that cholinergic treatments are of clinical importance against early-stage Alzheimer's disease and mild cognitive impairments.